Self-sensing and mechanical properties of engineered cementitious composites incorporating carbon nanofiber-coated Polyethylene fibers - Mak, Benjamin Jun-Wei (2019)
Research on self-sensing Engineered Cementitious Composites (ECC) has been ongoing as it is a crucial alternative for structural health monitoring due to its excellent mechanical properties as well as being capable of sensing strain by showing changes in electrical resistivity. Past research has shown that by modifying the interface between fiber and matrix, the mechanical and sensing properties of the matrix can be improved. A different technique of modifying the fiber-matrix interface by coating the surface of Polyethylene (PE) fibers with Carbon-Nanofiber (CNF) through hydrophobic interactions first before dispersion into ECC, was proven to increase the mechanical properties of ECC. In this paper, this technique will be adopted into M45 ECC to investigate whether this method could increase the piezoresistivity of ECC as well as its mechanical strength. The resistivity of ECC added with CNF is measured through a four-probe method under uniaxial tensile loading. The effects of CNF coated PE fibers on the initial bulk resistivity and relative change in resistivity will be assessed to determine how sensitive the material is to strain changes.